Prescribing patterns and persistence of biological therapies for psoriasis management: a retrospective cohort study from Saudi Arabia - Ahmad Alamer; Wejdan Alyazidi; Saad Aldosari; Fatimah Mobarki; Sarah Almakki; Abdullah Alahmari; Mukhtar Alomar; Ziyad Almalki; Tuqa Alkaff; Mohammad Fazel (Journal of Dermatological Treatment)
Background Biological therapies are effective for psoriasis, but patient responses vary, often requiring therapy switching or discontinuation.Objectives To identify physicians’ prescribing patterns of biological therapies at a referral tertiary center in Saudi Arabia and assess the probability of biologic persistence following treatment initiation.Methods We conducted a retrospective study of biologic-naïve adult psoriasis patients who initiated therapy from October 2013 to July 2022 in Dammam. Descriptive statistics and a Kaplan-Meier analysis evaluated treatment persistence at 6, 12, 24, and 36 months.Results A total of 151 patients received adalimumab (n = 89), etanercept (n = 17), risankizumab (n = 30), ustekinumab (n = 14), and ixekizumab (n = 1). At 6 months, all therapies demonstrated 100% persistence. At 12 months, persistence was highest for ustekinumab (100%) and lowest for etanercept (88.2%). At 24 months, ustekinumab maintained 100% persistence, followed by risankizumab (96.6%), adalimumab (94.3%), and etanercept (76.4%). At 36 months, risankizumab had the highest persistence (96.6%), followed by adalimumab (83.1%), ustekinumab (78%), and etanercept (70.6%). The most common reasons for discontinuation were lack of effectiveness and intolerability.Conclusion This study shows changing psoriasis treatment patterns with new therapies. Risankizumab demonstrated high long-term persistence, while etanercept and ustekinumab showed declining persistence, suggesting evolving treatment considerations.